Journeys Across Difference: Pre-service Teacher Education Students’ Perceptions of a Pedagogy of Discomfort in a Digital Storytelling Project in South Africa - Gachago, Daniela; Ivala, Eunice; Condy, Janet; Chigona, Agnes (Critical Studies in Teaching and Learning, 2023)
Engaging with difference is an important skill for teachers in current South Africa. Critics of the dominant approach to teaching on and with difference in pre-service teacher education argue that it mostly promotes de-contextualised celebrations of diverse cultures without addressing critical issues of power and social forces. One of the reasons that educators shy away from engaging with issues of power and privilege in the classroom is the fear of highly explosive emotions that might emerge in the process. In South Africa this is compounded by the legacy of racial discrimination, still impacting on today’s social engagements of students. However, proponents of the ’affective turn’ (Berlant 2008; Ahmed 2004; Ahmed 2010; Clough and Halley 2007; Gregg and Seigworth 2010) in the Social Sciences argue, that it is important to work with the emotions that govern our classrooms, for social transformation in students to happen. Boler and Zembylas’ ’pedagogy of discomfort’ (2003) for example stipulates that for social transformation to happen both students and educators have to step out of their comfort zone, to experience discomforting emotions, and recognizes the value of both cognitive and emotional labour for learning about difference. This study is piloting an innovative approach for teaching on and with difference in a South African pre-service teacher education classroom, combining a digital storytelling process with participatory learning and action techniques and a reflective essay. Framed by Boler and Zembylas’ (2003) work on the politics of emotions and feminist writings on the role of affect and public feelings, we explored how students experienced and negotiated their cognitive and emotional journey in this project. An interpretive analysis of data collected through focus groups with selected students revealed that this classroom was a highly divided, complex and contested space, in which students identified strongly along racial background and actively constructed entities in opposition to each other. However, through the creation of disruptive moments of sharing and listening openly to each others’ stories, students began to critically engage with the unspoken emotional rules and power dynamics governing the classroom and their lives. Further research would be valuable to explore the long term potential of this pedagogical intervention towards social change.